2015
DOI: 10.1007/s00586-015-4198-1
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive cervical foraminotomy and diskectomy for laterally located soft disk herniation

Abstract: For patients with foraminal soft-disk herniation, either MTPF or P-PECD, may be regarded as an alternative options to open surgery. Preoperative kyphotic SA (cut-off value 1.45°) seemed to be associated with poor outcome and this may be considered in selecting surgical methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(92 citation statements)
references
References 38 publications
2
89
1
Order By: Relevance
“…All of the patients who had an adequate follow-up have had no recurrence thus far. Some authors reported that preoperative kyphotic SA (cut-off value 1.45°, sensitivity 80%, specificity 73%) seemed to be associated with a poor outcome, however the sample size of the study was only 22 (28). On the univariate analysis clinical factors affecting prognosis in our study, there was no significant difference between the preoperative kyphotic SA (< 1.45°) group and SA (≥ 1.45°) regarding excellent outcomes.…”
Section: E221contrasting
confidence: 62%
“…All of the patients who had an adequate follow-up have had no recurrence thus far. Some authors reported that preoperative kyphotic SA (cut-off value 1.45°, sensitivity 80%, specificity 73%) seemed to be associated with a poor outcome, however the sample size of the study was only 22 (28). On the univariate analysis clinical factors affecting prognosis in our study, there was no significant difference between the preoperative kyphotic SA (< 1.45°) group and SA (≥ 1.45°) regarding excellent outcomes.…”
Section: E221contrasting
confidence: 62%
“…C urrently, there are various options for the treatment of cervical radiculopathy due to lateral soft disc herniation or foraminal stenosis (1)(2)(3)(4)(5)(6)(7)(8). Analgesic medication, epidural steroid injection, and/or other procedures are the initial treatments of choice, but surgery may be considered when such conservative options are not effective (7,8).…”
mentioning
confidence: 99%
“…In patients suffering from soft lateral disk herniation both minimally invasive techniques show equal results in the patients' outcome and complication rates [9]. Furthermore, recent studies could show good clinical results for endoscopic posterior cervical foraminotomy in patients suffering from bony foraminal stenosis [5,[12][13][14].…”
Section: Discussionmentioning
confidence: 99%